Effectiveness of psychological interventions on mental health, quality of life and relationship satisfaction for individuals and/or couples undergoing fertility treatment: a systematic review and meta-analysis protocol - Katherine Bright; Loveness Dube; K Alix Hayden; Jennifer L Gordon (BMJ Open)
Introduction Infertility is a global public health problem affecting men, women and couples worldwide. The medical implications of infertility are often of primary focus in healthcare settings, but the experience of infertility also has a considerable social, emotional and psychological impact. Interventions aimed at alleviating psychological symptoms in individual and/or couples undergoing fertility treatment requires a systematic and comprehensive review of the literature to determine the efficacy of psychological interventions. The objective of this review is to evaluate the effectiveness, feasibility and acceptability of psychological interventions for individuals and/or couples seeking fertility to treat anxiety, depression, distress, quality of life and relationship satisfaction, as well as improve pregnancy rates.Methods and analysis The search strategy will involve 11 databases, including MEDLINE(R) and Epub Ahead of Print, In-Process & Other Non-Indexed Citations and Daily (Ovid), EMBASE (Ovid), PsycINFO (Ovid), Cochrane Central Register of Controlled Trials (OVID), The Cumulative Index to Nursing and Allied Health Literature (CINAHL) with Full Text (EBSCO), Social Work Abstracts (EBSCO), SocINDEX with Full Text (EBSCO), Academic Search Complete (EBSCO), Family & Society Studies Worldwide (EBSCO), Family Studies Abstracts (EBSCO) and Scopus. These databases will be searched from their inception to September 2019. Independent reviewers will search peer-reviewed published studies through electronic databases and additional sources, will extract the data and assess the methodological quality. Random-effects meta-analysis will be carried out by calculating effect sizes as Cohen’s d indices. Heterogeneity will be examined by the I2 and the Q statistics.Ethics and dissemination The current review does not require ethics approval. The results will be disseminated through publications in peer-reviewed journals.PROSPERO registration number CRD42019133757.